1956
DOI: 10.2134/agronj1956.00021962004800050008x
|View full text |Cite
|
Sign up to set email alerts
|

Some Applications of the Thermoelectric Method for Measuring Water Flow Rates in Plants1

Abstract: SYNOPSISMaximum transpiration rates for cotton plants were found to occur when relative humidities varied between 42 and 50%, temperatures from 95 to 100 F., and wind velocities between 1 and 4 miles per hour. Soil moisture tension appeared to control absorption and movement of water in plants.F ACTORS which cause a reduction in water absorption or transpiration will likewise affect the rate of water movement through .the plant ( 1, 4, 7). In order to evaluate the influence of such factors, a thermoelectric me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1957
1957
1991
1991

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 5 publications
2
9
0
Order By: Relevance
“…This conclusion is also supported by measurements of flow velocity in herbs and shrubs using the heat pulse technique Schmidt, 1936,1937). Zimmermann and Brown (1980) reported that the L-value determined experimentally was one magnitude smaller than the value calculated theoretically (see also Bloodworth, 1956;Wendt et al, 1965). Interestingly, the average flow velocity of 2.8 * m -s-l measured by the heat pulse technique (Huber, 1932) agrees very well with the value of 2.5 -m -s-l reported here.…”
Section: Discussionsupporting
confidence: 82%
“…This conclusion is also supported by measurements of flow velocity in herbs and shrubs using the heat pulse technique Schmidt, 1936,1937). Zimmermann and Brown (1980) reported that the L-value determined experimentally was one magnitude smaller than the value calculated theoretically (see also Bloodworth, 1956;Wendt et al, 1965). Interestingly, the average flow velocity of 2.8 * m -s-l measured by the heat pulse technique (Huber, 1932) agrees very well with the value of 2.5 -m -s-l reported here.…”
Section: Discussionsupporting
confidence: 82%
“…This is mainly because it is simple and accurate compared with other methods, as described by Slavik (1974). For example, Kuniya(1950), Bloodworth(1955;1956), Closs(1958), Ledefoged (1960), Kobayashi(1963), Decker and Skau (1964), Skidmore and Stone (1964), Wendt et al (1965), Swanson (1972), Morikawa (1972;, Shaw and Gifford (1975), Stone and Shirazi (1975), and Schurer et al (1979) have used the heat pulse method to study the water velocity in the trunk of arbores or in the stem of herbaceous plants in relation to environmental conditions. However, as pointed out by Marshall (1958), the heat pulse method has a fundamental disadvantage in that the measured pulse velocity is different from the stream velocity of water in a trunk or stem of plants.…”
Section: Introductionmentioning
confidence: 99%
“…Plant water deficits may induce both leaf and boll abscission from cotton under field conditions (5,6,18). In most instances, actual separation follows relief from the deficit and rehydration of the abscission zone.…”
mentioning
confidence: 99%